2012
DOI: 10.1007/978-3-642-32775-9_19
|View full text |Cite
|
Sign up to set email alerts
|

SMEs’ Perception of Cloud Computing: Potential and Security

Abstract: Abstract. Cloud computing is a new paradigm for emerging technology in the computing and IT industries. Cloud computing offers a new pathway for business agility and supports a faster time to market by offering ready-toconsume cloud-based IT services. SMEs can wisely take advantage of the cloud computing services, without the need for upfront costs. The perception of cloud computing from an SME stance is explored. The potential and concerns surrounding the adoption of cloud computing are discussed. A survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 12 publications
1
22
0
1
Order By: Relevance
“…Within this category privacy and confidentiality scored the highest with an average rate of 4.21 followed by the concerns of losing control rated at 4.09, and the concerns of vendor lock-in scored an average rating of 3.73. This result substantiates similar studies that conducted at the beginning of cloud adoption such as [13][14][15]. Therefore, security, fear of losing control, and vendor lock-in are still perceived by many as issues deterring migration.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Within this category privacy and confidentiality scored the highest with an average rate of 4.21 followed by the concerns of losing control rated at 4.09, and the concerns of vendor lock-in scored an average rating of 3.73. This result substantiates similar studies that conducted at the beginning of cloud adoption such as [13][14][15]. Therefore, security, fear of losing control, and vendor lock-in are still perceived by many as issues deterring migration.…”
Section: Resultssupporting
confidence: 87%
“…Further, many previous studies explored the business benefits and barriers for adoption. They focused mostly on the cost benefits, scalability, agility and the security issues, for examples see [13][14][15][16][17]. While these studies identified some factors that influence the decisions to migrate to the cloud, they were developed at an early stage of the evolvement of cloud computing.…”
Section: Introductionmentioning
confidence: 99%
“…Sarwar and Khan (2013) found that security is the biggest issue in Cloud computing as, while utilising storage service in a remote location, the consumers are generally unaware of what happens to their data. According to Forrester research, Sahandi et al (2012) reported that security concerns are the most commonly cited reason why enterprises are not interested in SaaS Cloud. Therefore, this study hypothesises that:…”
Section: Cloud Securitymentioning
confidence: 99%
“…In most Cloud service scenarios, consumers have no idea where their data are stored, due to the dynamic nature of the Cloud (Pearson & Benameur, 2010). Legal and regulatory issues arise that require careful consideration, because the physical location of data centres determines the set of laws that govern the management of data (Sahandi, Alkhalil & Justice, 2012). It is also interesting to note that IT adoption mainly refers to in-house IT infrastructure, whereas Cloud computing adoption involves accessing resources outside the organisation via the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud computing has been perceived by many enterprises as the solution to drive businesses growth, support faster time to market, using reduced IT resources as well as lower costs. This has resulted in cloud computing being rapidly adopted by enterprises of different sizes and from various sectors [2].…”
Section: Introductionmentioning
confidence: 99%